Swelling effect on coal micro structure and associated permeability reduction - Zhang, Y.; Lebedev, Maxim; Sarmadivaleh, Mohammad; Barifcani, Ahmed; Rahman, T.; Iglauer, Stefan (Elsevier Ltd, 2016)
© 2016 Elsevier Ltd. All rights reserved.Porosity and permeability of deep unmineable coal seams are key parameters in the context of (enhanced) coalbed methane recovery and CO2 geo-storage in coal beds as they determine productivity and injection rate. Porosity and permeability are again determined by the micro-structure of the coal, and the cleat network-coal matrix system. Furthermore, it is well established that swelling of the coal matrix due to water adsorption can significantly reduce permeability. However, the exact effect of swelling due to water adsorption on the coal micro-structure is only poorly understood, and how this microstructural change impacts on the permeability and porosity characteristics of the coal. We thus imaged dry coal plugs and swollen coal plugs (swollen due to brine adsorption) at high resolution (3.43 µm3) in 3D with an X-ray micro-computed tomograph (microCT). On the microCT images two types of cleats were identified; cleats in the coal matrix and cleats syngeneic with the mineral phase. Approximately 80% of the coal matrix cleats closed upon water adsorption, while the cleats in the mineral phase were not affected. This cleat closure by water adsorption dramatically reduced porosity and particularly permeability, consistent with dynamic permeability core-flood measurements.